1997
DOI: 10.1057/palgrave.jibs.8490103
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Diversity and the Performance of Multinational Firms

Abstract: We test the hypothesis that culturally related international diversification will have a positive impact on firm performance and that the opposite will be true for culturally unrelated globalization. Cultural diversity for Fortune 500 firms was used to predict performance over a ten-year period (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994), controlling for several organizational and industry characteristics. Regression tests using nine indicators of cultural diversity revealed no significant cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
188
1
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 416 publications
(197 citation statements)
references
References 73 publications
2
188
1
6
Order By: Relevance
“…COL was negatively related to receptivity to distance learning technology (Anakwe et al, 1999), and was positively related to perceptions of an organization's readiness to change to team-based selling (Eby et al, 2000) in the US. Using Hofstede's (1980a) country scores to assign cultural values to Li and Guisinger (1991) main , Datta and Puia (1995) main , Barkema et al (1996) main , main , main , Gomez-Mejia and Palich (1997) Geletkanycz (1997) found that managers were more likely to believe that the future chief executive officer (CEO) of their company should have the same expertise as the current CEO, and that the company's future corporate strategy should be the same as the existing corporate strategy (i.e., essentially demonstrating acceptance of the status quo) when they were high on IND, and low on UA, PD, and longterm orientation.…”
Section: Research Incorporating Hofstede's Cultural Value Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…COL was negatively related to receptivity to distance learning technology (Anakwe et al, 1999), and was positively related to perceptions of an organization's readiness to change to team-based selling (Eby et al, 2000) in the US. Using Hofstede's (1980a) country scores to assign cultural values to Li and Guisinger (1991) main , Datta and Puia (1995) main , Barkema et al (1996) main , main , main , Gomez-Mejia and Palich (1997) Geletkanycz (1997) found that managers were more likely to believe that the future chief executive officer (CEO) of their company should have the same expertise as the current CEO, and that the company's future corporate strategy should be the same as the existing corporate strategy (i.e., essentially demonstrating acceptance of the status quo) when they were high on IND, and low on UA, PD, and longterm orientation.…”
Section: Research Incorporating Hofstede's Cultural Value Dimensionsmentioning
confidence: 99%
“…Interestingly, others found that cultural distance did not affect initial or subsequent FDI decisions (Benito and Gripsrud, 1992); the type of cooperative arrangements of firms across borders (Pan and Tse, 1996); the choice between acquisitions, greenfields (Brouthers and Brouthers, 2000), alliance performance (Glaister and Buckley, 1999), firm performance (Gomez-Mejia and Palich, 1997), amount of FDI (Habib and Zurawicki, 2002), or abnormal return as a result of US international JV (IJV) announcement (Merchant and Schendel, 2000) or after FDIs are made (Kallunki et al, 2001). On the contrary, larger cultural distances were related to lower JV dissolution rates (Park and Ungson, 1997), higher IJV (Pothukuchi et al, 2002), and cross-border acquisition performance (Morosini et al, 1998), decreased preference for greenfields (Nachum, 2003), and increased FDI into Mexico (Thomas and Grosse, 2001).…”
Section: Research Challengesmentioning
confidence: 99%
“…Рентабельность активов (return on assets -ROA), харак-теризующая отдачу от использования всех активов организации (банка), рассчиты-валась как отношение чистой прибыли к общим активам [Gomez-Mejia, Palich, 1997]. Рентабельность капитала (return on equity -ROE), отражающая эффек-тивность использования капитала, рас-считывалась как отношение чистой при-были к собственному капиталу [Rodsutti, Swierczek, 2002].…”
Section: этапы анализа данныхunclassified
“…This leads to the headquarters' desire for hierarchical control. Technocratic mechanisms, however, may reduce the ability of subsidiaries to adapt themselves to the local conditions (e.g., Doz & Prahalad, 1988;Gomez-Mejia & Palich, 1997;Hamilton & Kashlak, 1999;. The delegation of parent-country nationals (expatriates) as a personal form of hierarchical control can also cause opportunistic behavior and agency problems because the expatriates may so strongly identify with the foreign operation ("going native") that they lose sight of headquarters' objectives and the global perspective (e.g., Tan & Mahoney, 2006;.…”
Section: Problem and Objectivesmentioning
confidence: 99%